Body Size, Habitat, and Diet of Freshwater Crabs Isolapotamon mindanaoense and Sundathelphusa miguelito (Crustacea: Brachyura) in the Municipality of Lake Sebu, South Cotabato, Philippines - Molina, Ziljih S.; Neri, Jemateo B.; Cañete, Rizza May P.; Metillo, Ephrime B. (Science Diliman: A Journal of Pure and Applied Sciences, 2020)
Isolapotamon mindanaoense  (Rathbun 1904) and  Sundathelphusa miguelito  Mendoza and Sy 2017 have narrow biogeographical distribution and are both regarded as endemic to Mindanao island. They are common and publicly consumed freshwater or semi-terrestrial crabs inhabiting vicinities near the waterfalls of Lake Sebu Municipality, South Cotabato in Mindanao, but both species are scarcely investigated. This study aimed to examine the body size, microhabitat and the feeding ecology of these freshwater crab species. Sex and carapace width and length of individuals were determined from specimens collected by hand at three waterfall sampling sites. Feeding and feeding niche overlap were respectively analyzed using the index of relative importance (IRI) of prey items from individual crab stomachs and the Schoener’s R o  index. Food items ingested include fish fragments, insect body parts, fragments of aquatic vascular plants, freshwater algae, sand grains and amorphous materials, and these items were similar between species. However, the larger  I. mindanaoense  appeared to ingest more fish fragments and other animal prey items compared to  S. miguelito  which ingested more amorphous materials that are derived from benthic plants. However, the R o value of 93% was high, suggesting very similar diet. The two species further partition niches, with  S. miguelito  being smaller in size and inhabiting sand and gravel substrate, while the larger  I. mindanaoense  inhabit areas with big boulders. Hence, the crabs can be categorized as omnivorous and detrivorous, and exhibit feeding and habitat niche partitioning that alleviate possible resource competition between the two species.
Keywords: Mindanao, feeding ecology, IRI, omnivory, niche partitioning, diet